An unusual indication for splenectomy in hairy cell leukaemia: a report of three cases with persistent splenomegaly after chemoimmunotherapy. (25th September 2015) - Sarid, Nadav; Ahmad, Humayun N; Wotherspoon, Andrew; Dearden, Claire E; Else, Monica; Catovsky, Daniel
Summary: We describe three cases of relapsed hairy cell leukaemia (HCL) treated with pentostatin plus rituximab. All three achieved bone marrow complete remission but had persistent splenomegaly and hypersplenism. Because of the clinical uncertainty of its significance, they were all splenectomized. The spleen histology showed no evidence of HCL, but a five‐fold thickening of the splenic capsule and areas of fibrosis in the red pulp. This process may have contributed to the lack of elasticity and caused the persistent splenomegaly. We discuss the clinical implications for future patient management. The three patients remain in remission at 1 + , 5 + and 9 + years.